2015
DOI: 10.1007/s10237-015-0749-y
|View full text |Cite
|
Sign up to set email alerts
|

Stress-shielding, growth and remodeling of pulmonary artery reinforced with copolymer scaffold and transposed into aortic position

Abstract: Ross operation, i.e., the use of autologous pulmonary artery to replace diseased aortic valve, has been recently at the center of a vivid debate regarding its unjust underuse in the surgical practice. Keystone of the procedure regards the use of an autologous biologically available graft which would preserve the anticoagulative and tissue homeostatic functions normally exerted by the native leaflets and would harmoniously integrate in the vascular system, allowing for progressive somatic growth of aortic struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(90 citation statements)
references
References 49 publications
3
87
0
Order By: Relevance
“…In our series, we reported a significant increase in diameters at the level of the sinus of Valsalva and STJ at 15 years follow‐up in nonreinforced PA as compared to reinforced autografts 3 . In in‐vivo studies using an experimental model of Ross operation, 9‐13 we demonstrated the physical‐mechanical relation between stress‐strain, somatic growth, and histological remodeling, highlighting the possibility of inducing changes to the properties of the PA by using a semiresorbable prosthesis consisting of expanded polytetrafluoroethylene and polydioxanone as external supports 8,14 …”
Section: Discussionmentioning
confidence: 61%
“…In our series, we reported a significant increase in diameters at the level of the sinus of Valsalva and STJ at 15 years follow‐up in nonreinforced PA as compared to reinforced autografts 3 . In in‐vivo studies using an experimental model of Ross operation, 9‐13 we demonstrated the physical‐mechanical relation between stress‐strain, somatic growth, and histological remodeling, highlighting the possibility of inducing changes to the properties of the PA by using a semiresorbable prosthesis consisting of expanded polytetrafluoroethylene and polydioxanone as external supports 8,14 …”
Section: Discussionmentioning
confidence: 61%
“…The previously developed mechanical model (see Ref. for a detailed mathematical description) well applied in this scenario providing a detailed description of the biomechanical changes occurring in the PA when reinforced with a composite prosthesis. As mentioned above, the reinforcement was constituted by a resorbable material, which histologically showed the ability to integrate with PA adventitial tunica and elicited the production of new extracellular matrix with high content in elastic fibers.…”
Section: Discussionmentioning
confidence: 99%
“…We pursued the reinforcement of the pulmonary artery autograft (PA) toward the creation of a NA with resorbable scaffold or composite semiresorbable armored prosthesis able to mediate a biomechanical effect and counteract the abnormal process of the extracellular matrix disruption leading to NA dilatation. We further revealed the mechanisms of growth, remodeling, and stress shielding of the reinforced NA root by means of an experimental large animal model supported by an ex vivo mathematical and physical model …”
Section: Introductionmentioning
confidence: 99%
“…This composite prosthesis prevented pulmonary autograft dilation while reabsorption of its PDS layer promoted a connective remodeling of the pulmonary autograft wall resulting in a neo-vessel formation, with increased elastin content and therefore potentially improved biomechanical properties. Moreover, application of a bio-resorbable reinforcement is able to modify the behavior of the curve of distensible materials, such as vessels wall, obtaining an increase of their elastic properties (41)(42)(43)46,49). Pre-clinical and clinical evaluations of the biomechanical properties of these reinforced pulmonary autografts might shed new light on the current debate about the long-term fate of the pulmonary autograft after Ross procedure, in order to improve the outcomes of the treated young patients.…”
Section: Future Directionsmentioning
confidence: 99%
“…Histologic analysis proved that loss and fragmentation of medial elastin fibers and increased adventitial collagen deposition occur after implantation (36)(37)(38). Since late autograft dysfunction remains a daunting issue in the Ross operation, our group and others tried to characterize the biomechanical aspects of pulmonary autograft failure (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) to understand in details the long-term effects and develop future frontiers in both surgical and basic researches.…”
mentioning
confidence: 99%